DINAMIKA INTERAKSI ANTARETNIK DALAM MEWUJUDKAN KESERASIAN SOSIAL DI WILAYAH PERBATASAN NEGARA INDONESIA - MALAYSIA - Agus Sikwan (Jurnal Sosial Humaniora, 2017)
The research reveals the dynamics of interaction between the three majorethnic groups (ethnic Dayak, Malay and Chinese) living in Entikong Subdistrict. These interactions are manifested in social relationships, ierelationships as relatives, as friends. Through qualitative analysis, therelationship is still strong in primordial loyalty among ethnic groups. It ischaracterized by a tendency to choose individuals from their own ethnicgroups to serve as relatives. The results also show that there are two forms ofethnic group settlements in Entikong Subdistrict, namely: Mixed pattern, iesettlement area in which consists of various ethnic groups, in which there ismore intensive inter-ethnic social contact that can encourage the realizationof harmony social; Separate pattern, ie settlement area which consists of oneethnic group of the same kind, generally inhabited by Chinese ethnic groups.The change of settlement pattern indirectly caused by the expansion of subdistricts and population growth.